1997
DOI: 10.1007/pl00009700
|View full text |Cite
|
Sign up to set email alerts
|

Needle CO2 exchange, structure and defense traits in relation to needle age in Pinus heldreichii Christ – a relict of Tertiary flora

Abstract: Needle CO 2 exchange, structure and defense traits in relation to needle age in Pinus heldreichii Christ ± a relict of Tertiary flora AbstractmPinus heldreichii Christ is a long-lived, slowgrowing Tertiary relict from the Balkans. In this study we evaluated the physiological characteristics of eight needleage classes of P. heldreichii grown at the Arboretum of the Institute of Dendrology in Ko Ârnik, Poland. At the end of the growing season, current-year foliage had the highest rates of mass-based light-satura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
32
2
3

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 34 publications
6
32
2
3
Order By: Relevance
“…We observed that P of detached 1-year-old A. alba needles did not significantly differ from P of attached 1-year-old needles. This observation is consistent with the results of gas exchange measurements on attached and detached needles of other conifer tree species (Oleksyn et al 1997;Maier et al 2002). A custom-made lamp consisting of sets of interspersed blue and red diodes was used as a cool light source with intensity controlled at the power adapter (Wyka et al 2008).…”
Section: Measurements Of Gas Exchangesupporting
confidence: 91%
See 2 more Smart Citations
“…We observed that P of detached 1-year-old A. alba needles did not significantly differ from P of attached 1-year-old needles. This observation is consistent with the results of gas exchange measurements on attached and detached needles of other conifer tree species (Oleksyn et al 1997;Maier et al 2002). A custom-made lamp consisting of sets of interspersed blue and red diodes was used as a cool light source with intensity controlled at the power adapter (Wyka et al 2008).…”
Section: Measurements Of Gas Exchangesupporting
confidence: 91%
“…(Weikert et al 1989), Pinus sylvestris L. (Freeland 1952;Wang et al 1995;Jach and Ceulemans 2000), Abies amabilis (Dougl.) Forbes (Brooks et al 1996), Pinus heldreichii Christ (Oleksyn et al 1997), Pinus taeda L. (Crous and Ellsworth 2004), Pinus pinaster Aiton (Warren 2006), Pinus densiflora Sieb. et Zucc.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Indeed, higher investments in defensive alkaloids can be found in younger leaves (Iwasa et al, 1996). However, older leaves can contain more tannins, which cannot be retranslocated to younger leaves (Oleksyn et al, 1997). Another sense of ' more valuable ' arises in comparing plants of different nutritional status.…”
Section: Nutritional Unattractiveness From Low Nutrient Contentmentioning
confidence: 99%
“…In these studies, light (Bond et al 1999, Palmroth and Hari 2001, Kobayashi and Gyokusen 2002, Han et al 2003a, nutrient availability (Reich and Schoettle 1988, Marshall et al 1994, Kobayashi and ---Gyokusen 2002, Ripullone et al 2003, and needle age (Brooks et al 1996, Oleksyn et al 1997, Schoettle and Smith 1999 were investigated as the source of variation in needle N content. However, each of these studies was conducted over a short period during a growing season under favorable conditions, and hence in evergreen conifers it remains unknown whether photosynthetic capacity correlates with needle N content considering the temporal changes in needles N content as the source of variation.…”
Section: Introductionmentioning
confidence: 99%